(untitled) (Journal of Rangpur Medical College, 2023)
Background: Sedentary lifestyle is an issue of great concern because of its deleterious health implication. It is associated with limited physical activity. Regular physical activity with good physical fitness are widely accepted as factors that reduce all cause of mortality and improve number of health outcome. Objective: To assess the cardiovascular sympathetic nerve function status by the cold pressor test in healthy adult male sedentary workers. Methods: This cross-sectional analytical study was conducted from January 2019 to December 2019 in the Department of Physiology, Rangpur Medical College, Rangpur. After obtaining permission, a total 60 subjects who were met the inclusion criteria was enrolled in the study after briefing them objectives of the study. Among them 30 were healthy adult male heavy workers (Group-A) and 30 were healthy adult male sedentary workers (Group-B). The basal systolic and diastolic blood pressure was recorded in resting condition. The evaluation of sympathetic nerve functions in selected individuals was done by cold pressor test. The individuals were selected from different areas of Rangpur district. For statistical analysis unpaired t-test was performed by computer-based software SPSS-23.0 version for windows. Results: The resting systolic and diastolic blood pressure are non-significant in selected individuals. Diastolic blood pressure response by cold pressor test was significantly lower in sedentary workers. (p< 0.05). Conclusion: The study thus concluded that decreased diastolic blood pressure response by cold pressor test in sedentary individuals indicate impairment of the sympathetic nerve function. J Rang Med Col. March 2023; Vol. 8, No. 2:59-64